Drama - Telgemeier, Raina (New York : Graphix, 2012)
Callie rides an emotional roller coaster while serving on the stage crew for a middle school production of Moon over Mississippi as various relationships start and end, and others never quite get going.
Includes bibliographical references.
Horn Book
Kirkus Starred
Pub Weekly
Horn Book, September 2012
Kirkus Starred, August 2012
Keywords: Interpersonal relations -- Comic books, strips, etc -- Juvenile fiction; Middle schools -- Comic books, strips, etc -- Juvenile fiction; Theater -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Theater -- Fiction; Comic books, strips, etc; Graphic novels; Interpersonal relations -- Comic books, strips, etc -- Fiction; Middle schools -- Comic books, strips, etc -- Fiction; School stories; Theater -- Comic books, strips, etc -- Fiction; Graphic novels